x+1+x*2=-6

Simple and best practice solution for x+1+x*2=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+1+x*2=-6 equation:


Simplifying
x + 1 + x * 2 = -6

Reorder the terms for easier multiplication:
x + 1 + 2x = -6

Reorder the terms:
1 + x + 2x = -6

Combine like terms: x + 2x = 3x
1 + 3x = -6

Solving
1 + 3x = -6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 3x = -6 + -1

Combine like terms: 1 + -1 = 0
0 + 3x = -6 + -1
3x = -6 + -1

Combine like terms: -6 + -1 = -7
3x = -7

Divide each side by '3'.
x = -2.333333333

Simplifying
x = -2.333333333

See similar equations:

| 7b^2-5b=0 | | -24+(-3)= | | y=0.5*-2+3 | | y=4x^3-6x^2+3 | | (8+z)(3z+1)=0 | | 4x^7v^3*2v^9*6x=0 | | y=6-2*-2 | | -6s=30 | | 6x+108=12x-12 | | y=6-2*2 | | 4x+4=x+1+x*2 | | 500x-340=30x-3677 | | 12-6s=30 | | 4s-2=-4+2s | | 3x-25x-x+45= | | 5x+3y=3000 | | 9000=92x(1.8)t | | y=-4*-2 | | 2ab+6bc= | | 2+(-3)+(-18)= | | (x^2-6)-(x-4)= | | 45=2v+9 | | 2f+32=94-38 | | 14.5=-16a-4(-3a-4) | | 10x^2-5xy=0 | | -14x+49=-5x+55-7x | | 3y+15=15 | | 5+25x=20x+9 | | (3+w)(2w+1)=0 | | 9x-7-2x=6-3x+7 | | 4x^3-3x^4=0.5 | | x*(x^2+2x-2.5)-5=0 |

Equations solver categories